Short and long term determinants of export diversification in Algeria: ARDL model (1995-2020) - Touati Karima; Keddari Nassim (Journal of North African Economies, 2025)
The object of this paper is to examine the determinants of the diversification of exports in Algeria over the period 1995-2020 using the ARDL model. The cointegration analysis revealed the presence of long-run relationship between export diversification and its determinants. The error correction model also revealed a short-run relationship among export and its determinants. The study found that all the explanatory variables had a long- run relationship with export diversification. Specifically, terms of trade had the expected negative sign. On the other hand, GDP growth and degree of freedom to invest found to affect, in long-term, negatively export diversification in Algeria. The short-term results showed that the positive drivers of export diversification are GDP growth and degree of freedom to invest. While terms of trade favours export specialization. These results suggest a diversification in the export basket, structural transformation of the Algerian economy and improvement of the business climate.